Ibandronate: a new option in osteoporosis treatment - Sewerynek, Ewa (Menopause Review/Przegląd Menopauzalny, 2006)
Osteoporosis is a highly prevalent skeletal disorder characterized by compromised bone strength predisposing individuals to an increased risk of fractures. Bone strength results from the combination of bone mineral density and bone tissue quality. Osteoporosis is a disease requiring systematic therapy, often over many years. There are several possible ways of prevention and therapy of osteoporosis. Beside pharmacological treatment, proper diet, lifestyle changes and physical activity play important roles as well. Biphosphonates are the drugs most often used in the therapy of osteoporosis. They improve bone mineral density and bone tissue microarchitecture, as well as reducing the risk of fractures. Despite the implementation of new therapeutic methods, they remain the basic group of drugs, while – in order to improve comfort of use and reduce side effects – the research of recent years attempts, first of all, to reduce the frequency and change the way of their administration. The use of ibandronate preparation once a month reduces the number of side effects of the gastrointestinal tract and improves tolerance to the drug. Administration of this new therapy in intravenous form allows for elimination of many adverse events, while improving the compliance of chronic treatment.